Antimicrobial activity and GC-MS analysis of bioactive constituents of Aspergillus fumigatus 269 isolated from Sungai Pinang Hot Spring, Riau, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Octarya Z, Novianty R, Suraya N, Saryono. 2021. Antimicrobial activity and GC-MS analysis of bioactive constituents of Aspergillus fumigatus 269 isolated from Sungai Pinang Hot Spring, Riau, Indonesia. Biodiversitas 22: 1839-1845. A total of 16 isolates of thermophilic fungi originating from hot springs in Riau and West Sumatra have been tested for their antimicrobial ability against pathogenic microbes Candida albicans, Staphylococcus aureus, and Escherichia coli. The antimicrobial test was carried out by using the disk diffusion method. Molecular identification of the most potential isolate (LBKURCC269) was carried out by amplifying the ITS (Internal transcribed spacer) sequence on rDNA using universal primer ITS-4 and ITS-5. ITS sequence results showed that LBKURCC269 has a 99% similarity to Aspergillus fumigatus. Ethyl acetate extract of LBKURCC269 (Aspergillus fumigatus 269) showed good antimicrobial activities against three pathogenic microbes tested with the inhibition of 17 mm, 13 mm, and 13 mm against Staphylococcus aureus, Candida albicans, and Escherichia coli, respectively. There were 24 identified chemical compounds in ethyl acetate extract. The major compounds were eicosane, eicosane 2-methyl, phenol, 2,6-bis(1,1-dimethyl ethyl)-4-methyl, hexadecane 2, and 11-octadecenoic acid, methyl ester. These findings suggest that thermophilic fungi isolated from hot springs could serve as reservoirs for new bioactive compounds of industrial and medical importance.
Keywords: Antibiotic, Aspergillus fumigatus, Bioactivity, GC-MS, Thermophilic fungi.